Socio-Political Development and Internal Security Management in Nigeria: An Appraisal of Northern Nigeria 2015-2020 - ONONIHU, Simon Chukasi; OKONKWO, Clement Nwafor (Socialscientia: Journal of Social Sciences and Humanities, 2022)
This paper observed alarming level of security challenges in Northern Nigeria and interrogated its logical nexus with socio-political development in the area and by extension of the polity, within the period under investigation. In undertaking the study, we generated our data from secondary sources through the documentary method of data collection. Subsequently, the data were empirically analyzed by the usage of textual analysis and logical deduction. We adopted the Social contract theory as the compass that guides the logical consequence of the study. The theory postulates a contract between the government and the governed thus making internal security management the responsibility of all the tiers of government. From the study, we found that internal security management in the North is over-centralized in the Federal purview and so ineffective. Hence the study proffers among others, the devolution of authority over internal security management, involving state and community policing. This will give all the tiers of government opportunity to effectively participate in security management, provide the needed local intelligence inputs and so engender a secure environment for socio-political development to thrive not only in the North but in the entire country.